2020
DOI: 10.1155/2020/9481720
|View full text |Cite
|
Sign up to set email alerts
|

Mangiferin Alleviates Renal Interstitial Fibrosis in Streptozotocin-Induced Diabetic Mice through Regulating the PTEN/PI3K/Akt Signaling Pathway

Abstract: Renal interstitial fibrosis is considered to be the typical manifestation of diabetic nephropathy (DN). Mangiferin has shown positive effect on the prevention or treatment of diabetes and its complications. The aim of this study was to explore the inhibitive effect and mechanism of mangiferin on renal interstitial fibrosis in diabetic mice. Streptozotocin- (STZ-) induced diabetic mice were treated with mangiferin (15, 30, and 60 mg/kg/d) for 4 weeks. The morphology of kidneys was observed by Masson’s trichrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 43 publications
3
33
0
1
Order By: Relevance
“…Similarly, in the present study, we found that PTEN not only inhibited the migration and invasion, and induced apoptosis of EC cells, but also reversed the effect of miR-25-3p on EC cells, which further confirmed that miR-25-3p regulated the migration, invasion, and apoptosis of EC cells by targeting PTEN. It's also well known that the activity of PTEN antagonizes the PI3K/AKT pathway to suppress cancer cell survival, which means that deficient PTEN expression leads to the PI3K/AKT pathway activation, thereby enhancing cell anti-apoptosis [33][34][35]. In investigating the down-stream mechanism of miR-25-3p mediated in EC in the present study, we also observed that enhanced PTEN expression suppressed the activation of the PI3K/AKT pathway, and miR-25-3p-induced decrease of PTEN expression further enhanced the PI3K/AKT pathway activation, while overexpression of PTEN could inhibit the effect of miR-25-3p on this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the present study, we found that PTEN not only inhibited the migration and invasion, and induced apoptosis of EC cells, but also reversed the effect of miR-25-3p on EC cells, which further confirmed that miR-25-3p regulated the migration, invasion, and apoptosis of EC cells by targeting PTEN. It's also well known that the activity of PTEN antagonizes the PI3K/AKT pathway to suppress cancer cell survival, which means that deficient PTEN expression leads to the PI3K/AKT pathway activation, thereby enhancing cell anti-apoptosis [33][34][35]. In investigating the down-stream mechanism of miR-25-3p mediated in EC in the present study, we also observed that enhanced PTEN expression suppressed the activation of the PI3K/AKT pathway, and miR-25-3p-induced decrease of PTEN expression further enhanced the PI3K/AKT pathway activation, while overexpression of PTEN could inhibit the effect of miR-25-3p on this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of this pathway with rapamycin decreases macrophage infiltration and CCL2 release [239]. Furthermore, in a mouse model of diabetes, the treatment with mangiferin reduced IL-6, TNF-α, and Il-1β expression by inhibiting PTEN/PI3K/Akt pathway [240].…”
Section: Pi3k/akt/mtormentioning
confidence: 98%
“…45 TG and TC were both independent risk factors for DN. 46,47 A network Mendelian randomization study showed a positive correlation between TG and CHD. 48…”
Section: Dovepressmentioning
confidence: 99%